Classification and Regression Modelling of Abdominal Convexity Morphology in Middle-Aged and Elderly Women (Journal of Fiber Bioengineering and Informatics, 2023)
Abdominal protrusion is increasingly common among middle-aged and elderly women, and the currentstandard sizing system fails to properly their body shape change. To improve the classification ofabdominal bulge morphology in middle-aged and elderly women and enhance the garment fit, thispaper screened 133 samples with abdominal bulge among 165 Chinese women aged 50-59 years oldbased on 3D anthropometric techniques and obtained abdominal morphological dimensions. Five mainmorphology parameters affecting abdominal convexity were summarized, and the abdominal morphologywas classified into four types for simulation. The abdominal regression models and girth fitting modelswere established and validated by combining the feature indexes related to pants. Results showed thateach abdominal convexity type has obvious and specific clustering characteristics, and the regressionmodels are valid and practical for personalized clothing development.
Keywords: Body Classification; Abdominal Convexity; Middle-aged and Elderly Women; Shape parameter; Regression Modelling; Cluster Analysis